Behaviour of stiff clayey soils using fracture mechanics approach - Fauziah, Miftahul (Curtin University, 2009)
Most of the conventional elastic plastic models of soils are based on continuum mechanics, however, for stiff, hard soils and soft rocks discontinuities develop under load, and since the models assume continuity, they would cease to apply. These discontinuities had not been accounted for in the continuum-based elastic plastic models. On the other hand, fracture mechanical theory may be used to advantage to replicate their behaviour. The behaviour of soil commonly is interpreted from conventional triaxial apparatus, whereas, testing of soil using the plane strain device would be more useful information, as more geotechnical field problems are basically occur in these situations.The present study has dealt with the investigation on the behaviour of saturated over consolidated clay as well as partially saturated clay, which represent the stiff and hard brittle clay by the use of a new biaxial device modified from conventional triaxial apparatus. In general, the apparatus was able to produce data which are in a good accordance with known soil behaviour of stiff clay. Shear band localization occurred in all test specimens of over consolidated clay. Specimen initiated to be discontinuous upon reaching the peak stresses. It is evident that specimen of partially saturated containing fissures had weaker shear strength as well as compressive strength.From point of view of the discontinuities that take places in the stiff clay, a model based on the unified model (Lo et al, 1996) and the elasto-plastic shear fracture model (Lo, et al, 2005) was used in this study. The problem may be dealth with one of brittle fracture of a three-phase specimen, where the matric suction is disrupted by tensile or shear loading. As a result the fracture toughness of the specimen would vary according to matric suction changes. A problem of plane strain compression testing was carried out to implement the model. The crack propagation simulation was resulted the same pattern with the experimental results on partially saturated kaolin clay.